LEGAL AND SOCIO-ECONOMIC ISSUES OF AUTOMATED ISLAMIC BANKING IN UGANDA: LESSON FROM INDONESIA - Aidonojie, Paul Atagamen; Adebayo, Adesoji Kolawole; Eregbuonye, Obieshi; Mukhlis, Muhammad Mutawalli; Ibeh, Success (Diponegoro Law Review, 2024)
The global surge in digital technology has revolutionized various sectors, including Islamic banking. While Indonesia has successfully incorporated digital automation into its Islamic banking system, Uganda's nascent Islamic banking system faces opportunities and challenges in adopting similar technologies. This study uses a hybrid research method with a conceptual approach to explore the prospects and challenges in automating Uganda's Islamic banking system by learning from Indonesia's progress. A total of 306 questionnaires were distributed to Ugandan respondents, and the data were analyzed descriptively and analytically. The findings show that automation has significantly improved the Islamic banking system in Indonesia, a model that Uganda can emulate. However, implementation in Uganda faces legal and socio-economic barriers that may affect its feasibility. This study recommends revising Uganda's legal framework to support and regulate a digitalized Islamic banking system while addressing socio-economic challenges. Ultimately, the study underscores that with the right reforms, automation can improve Uganda's Islamic banking landscape.